Vitamin D3 And Irritable Bowel Syndrome: Review - Maryam Kadhim Al-Shemery; Fatema Ali Al Kafhage; Rusul Ali Al-Masaoodi (The International Science of Health Journal, 2024)
Irritable bowel illness is a widespread health ailment that affects almost every age group around the world. The pathogenesis of IBS is still poorly understood. It is a prevalent dysfunctional bowel condition marked by recurring stomach pain or discomfort and changed bowel habits. A central concept is that IBS symptoms are caused by a bilateral imbalance of brain-gut connections, which appears as increased gut sensation and changed bowel patterns. The purpose of the review is to determine the role of vitamin D levels in people with irritable bowel syndrome patients. Vitamin D, which plays a role in inflammatory processes, can affect a variety of pathways implicated in the appearance of IBS. Vitamin D insufficiency was shown to be greater in the IBS group, indicating a relationship between vitamins.